The Effect of Giving Physical Punishments to Student Awareness of As-Shakireen School, Waeng, Narathiwat, South Thailand - Ria Yulian; Slamet Hariyadi; Nuainee Awaesoh (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2019)
One of the requirements for the process of conducting education can take place effectively, namely the enforcement of student discipline both in attendance and participation in the education process, namely the application of punishment. The aim of this study is to determine the impact of punishment on students, the method is descriptive method, because the descriptive method intends to solve the problem of describing something state / subject based objects on what it is. The form of research is an interrelationship study, namely by conducting data collection. The result of this study is percentage that has a comparative analysis of mild and severe penalties in the form of a ratio. Respondents clearly stated that physical punishment had an effect on students' academic / career achievements (65%) while mild physical punishment had an adverse negative impact (35%). Looking further at the effects of physical punishment, it was observed that severe and severe penalties prevented class participation, reduced attendance and increased the dropout rate shown by respondents as wise. According to the explanation above, it can be concluded that the application of penalties, especially physical punishment to students will make students feel depressed and afraid that will have an impact on student psychology.